Incorporating energy generation process in environmental assessment of a biopharmaceutical process - Auni Hamimi, Idris (2015)
Biopharmaceutical industries consistently applied Water for Injection (WFI) as a solvent during their production stage. Generally, water is considered as non-hazardous material, but in the pharmaceutical industries the involved treatments to produce WET typically consumes a large amount of energy. This energy usually comes from the use of utility steam as well as electricity to heat the water as part of the purification process. Consequently, generation of utility steam and electricity needed to produce WFI releases gas pollutants and directly affecting the environment. However, such potential environmental impact (PEI), which is associated to the demand of WFI in a biopharmaceutical process, is typically not included in the environmental assessment of the process as water is considered benign. Therefore, this work aims to estimate the PET value from WFT and pure steam generation using a simple algorithm which is modified from Waste Reduction (WAR) Algorithm. The PEI is estimated based on the gas pollutants emitted from the energy generation process, which is in this case, the electricity and utility steam. In order to determine the energy needed in WET and pure steam generation, their generation system was modelled and simulated in SuperPro Designer®. WFI is typically produced in Multiple Effect Distillation (MED) system or Vapour Compression Distillation (VCD) system and meanwhile pure steam is produced in pure steam generator (PSG). A hypothetical large-scale of monoclonal antibody (MAb) production is used as a case study to demonstrate the environmental impact assessment using WAR Algorithm inclusive of PET from WFI and pure steam demand during manufacturing process. From the case study, it can be concluded that the WET generation, regardless of using MED or VCD, occupied the largest percentage of energy consumption. The PET shows a major contribution to the total PET value, particularly in global warming potential. The hotspot based on the highest WET consumption is Protein A chromatography. This equipment is used in the downstream processing step to purify the target product. As biopharmaceutical process needs a large amount of WET in the process, therefore it is important to include PET from WFI as part of the environmental assessment. This result is essentially useful as a tool for decision-making in order to create a more sustainable process.